THE CONCEPT AND EVOLUTION OF DIGITAL BANKING SERVICES - Ashurova Shakhzoda Shavkatovna; Meyliyeva Mutabar Farruxovna (Modern American Journals, 2025)
This article explores the concept and evolution of digital banking services, focusing on Uzbekistan’s transition to a modernized financial infrastructure. It examines the historical development of digital banking, global innovations, and local implementations. Additionally, it analyzes cybersecurity challenges, user adoption, and institutional readiness. Drawing on global case studies and national data, the study highlights both opportunities and constraints in the digital transformation of banking. The article also provides data-driven insights and graphical representations of digital banking trends, offering a comprehensive assessment of its impact and future potential.
Keywords: Digital banking, financial technology, cybersecurity, mobile banking, online banking, fintech, economic development.